Dual-constituent anti-tetra-chiral lattice metamaterial with tailorable coefficient of thermal expansion and excellent bandgap. (March 2023) - Bai, Liang; Wang, Wei; Xu, Weikai; Cheng, Saiwei; Yu, Xiaoming
Abstract: With the rapid development of engineering machinery, the constituent or protective structures of machinery serve in increasingly complicated work conditions. This puts higher demands on the multifunctionality of materials and structures. In this paper, a novel dual-constituent anti-tetra-chiral lattice metamaterial (DATLM) is designed to have both customizable negative Poisson's ratio (NPR), tailorable coefficient of thermal expansion (CTE), and good bandgap properties by introducing a partially curved bi-layer rib and exploiting the property of anti-tetra-chirality. The Poisson's ratio and effective Young's modulus of the anti-tetra-chiral lattice metamaterials can be derived from Castigliano's second theorem, and the effective thermal expansion coefficient is derived from the thermal deformation coordination and geometry relationship of the partially curved bi-layer ribs. The analytical and numerical solutions show good agreement, which will provide guidance and convenience for material design. Finally, the bandgap structures with negative CTE and NPR configurations are studied, and the effects of each geometric parameter on the bandgap are discussed. This research proposes a novel approach to the multifunctional design of mechanical metamaterial. Graphical Abstract: ga1